A robust guaranteed time slots allotment scheme for real-time and reliable communication in WBANs. (18th February 2021) - Soni, Gulshan; Selvaradjou, Kandasamy
The ever-increasing aging population and expenditure related to healthcare, consequently demand the requirement for a state-of-the-art healthcare system. Wireless body area networks (WBANs) are the potential contender for this requirement. The IEEE 802.15.4 standard is considered a suitable protocol for WBANs and its beacon-enabled mode supports real-time traffic through guaranteed time slots (GTS) feature. Nevertheless, it suffers from reliability and timeliness guarantees. To address this issue, this work advocates a robust guaranteed time slots allotment scheme (RGAS) that consists of two phases, viz.: 1) determination of the severity of sensor data using fuzzy inference system; 2) dynamic allocation of available GTS slots to the contending nodes. Through simulation results, we demonstrate that the proposed RGAS significantly outperforms the existing GTS mechanism specified in the IEEE 802.15.4 in terms of various performance metrics such as packets transmission, packet reception rate, packet loss rate, and effective utilisation of contention free period.